2007
DOI: 10.2987/5663.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bacillus Sphaericus With Improved Efficacy Against Culex Quinquefasciatus

Abstract: A Bacillus sphaericus highly toxic to 4th-stage Culex quinquefasciatus was isolated from sediment samples collected at Winter Beach marsh in Indian River County, Florida. This isolate, named WBM 1-1-13, showed significantly higher toxicity compared with strain 2297. WBM 1-1-13 is equivalent, though better initially, to the toxicity of strain 2362, the active ingredient of VectoLex. Furthermore, the Winter Beach marsh isolate produced more Bin per unit medium than strain 2362, which suggests that this new isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In addition, phase-contrast microscopy showed that the 1.1-kb insertion also reduced the size of the Bin crystal (data not shown). When B. sphaericus strains were tested against fourth-instar larvae of Culex quinquefasciatus using established methods (18)(19)(20), the 50% and 95% lethal concentrations of recombinant strain 2297DSIN were significantly higher than those of wild-type strain 2297, supporting the results obtained with SDS-PAGE, spore count data, and phase-contrast microscopy ( Table 1). Despite many attempts, very little has been revealed regarding the molecular mechanisms that regulate Bin synthesis and crystallization in B. sphaericus (1,6,8,24).…”
supporting
confidence: 74%
“…In addition, phase-contrast microscopy showed that the 1.1-kb insertion also reduced the size of the Bin crystal (data not shown). When B. sphaericus strains were tested against fourth-instar larvae of Culex quinquefasciatus using established methods (18)(19)(20), the 50% and 95% lethal concentrations of recombinant strain 2297DSIN were significantly higher than those of wild-type strain 2297, supporting the results obtained with SDS-PAGE, spore count data, and phase-contrast microscopy ( Table 1). Despite many attempts, very little has been revealed regarding the molecular mechanisms that regulate Bin synthesis and crystallization in B. sphaericus (1,6,8,24).…”
supporting
confidence: 74%
“…Mosquitocidal activities of VB17 and VB24 were determined in two steps. Preliminary mosquito bioassays were performed by growing both isolates in 50 ml of MBS medium (Park et al, 2007) for 3 days at 30°C and by using early 4th instar Aedes taeniorhynchus and Culex quinquefasciatus maintained at John A. Mulrennan, Sr., Public Health Entomology Research & Education Center, Florida A&M University. Growth and sporulation of both isolates were poor when other sporulation media such as GYS and NBG (Park et al, 2008) were used and, therefore, MBS was used for the rest of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Within the 49 flagellar L. sphaericus serotypes initially described (de Barjac et al, 1980), only nine of them contained mosquitocidal strains. Nowadays, most commercial L. sphaericus biopesticides against mosquito larvae are based on strains 2362 and C3-41 (Park et al, 2010), although continuous prospecting may help identify new isolates with higher entomotoxicity (Park et al, 2007). Mosquitocidal activity in L. sphaericus strains is mostly determined by the production of crystal binary (Bin) and soluble mosquitocidal toxin (Mtx) insecticidal proteins.…”
Section: Biology Of Commercial Bacterial Entomopathogensmentioning
confidence: 99%